ANALISIS MAQASID SYARIAH DALAM PENGEMBANGAN PRODUK PADA BANK SYARIAH INDONESIA (BSI) DI KOTA SAMARINDA - Jannah, Miftahul; Kamsiah, Kamsiah (Ekonomi Syariah STAI Sangatta Kutai Timur, 2023)
Bank Syariah Indonesia was established on May 17, 2000. Although Sharia banking products and services have grown rapidly in recent years, there are still obstacles, such as the lack of public knowledge about Sharia banking products and services. This is because some people still prefer conventional banking products that are considered more familiar and easier to understand. The purpose of this research is to identify the products available at Bank Syariah and analyze their Shariah Maqasid and strategies. The study was conducted from September 2022 to February 2023 at 5 BSI branch offices in Samarinda. The research method used was a descriptive study with a qualitative approach, and the data was collected through documentation analysis of the BSI products available on its official website. The data was then analyzed using Miles and Huberman's formula. The results showed that BSI's products include Hifz al-Maal savings account, Ishlah (improvement) Mudharabah deposit, Tazkiyah (purification) Sharia financing, Hifz al-Maal (wealth protection) Sharia credit card, Kaffah (balance) Sharia home financing, and Sharia investment to maintain balance and community welfare. The strategies that can be taken to promote Sharia banking include improving product quality, developing technology-based products that meet the needs of the public, and collaborating with the government.